Update 3.1 to FonaDyn — a system for real-time analysis of the electroglottogram, over the voice range - Sten Ternström (SoftwareX, 2024)
The human voice is notoriously variable, and conventional measurement paradigms are weak in terms of providing evidence for effects of treatment and/or training of voices. New methods are needed that can take into account the variability of metrics and types of phonation across the voice range. The “voice map” is a generalization of the Voice Range Profile (a.k.a. the phonetogram), with the potential to be used in many ways, for teaching, training, therapy and research. FonaDyn is intended as a proof-of concept workbench for education and research on phonation, and for exploring and validating the analysis paradigm of voice-mapping. Version 3.1 of the FonaDyn system adds many new functions, including listening from maps; displaying multiple maps and difference maps to track effects of voice interventions; smoothing/interpolation of voice maps; clustering not only of EGG shapes but also of acoustic and EGG metrics into phonation types; extended multichannel acquisition; 24-bit recording with optional max 140 dB SPL; a built-in SPL calibration and signal diagnostics tool; EGG noise suppression; more Matlab integration; script control; the acoustic metrics Spectrum Balance, Cepstral Peak Prominence and Harmonic Richness Factor (of the EGG); and better window layout control. Stability and usability are further improved. Apple M-series processors are now supported natively.